Tailoring rubber-filler interfacial interaction and multifunctional rubber nanocomposites by usage of graphene oxide with different oxidation degrees. (1st September 2017) - Wen, Yanwei; Yin, Qing; Jia, Hongbing; Yin, Biao; Zhang, Xumin; Liu, Pengzhang; Wang, Jingyi; Ji, Qingmin; Xu, Zhaodong
Abstract: In this paper, graphene oxide (GO) with different oxidation degrees were prepared by a modified Hummers' method, and were filled into carboxylated acrylonitrile butadiene rubber (XNBR) by latex co-coagulation method. The impact of oxidation degrees on the structure of GO, the interaction between GO and XNBR, the mechanical properties and thermal conductivity of XNBR nanocomposites were investigated. The results indicated that interfacial interaction between XNBR and GO became stronger with the increase of oxidation degrees of GO due to more oxygen-containing groups forming on the GO sheets and hydrogen bonding in the XNBR/GO nanocomposites, which led to a better dispersion of GO in rubber matrix as well as improved mechanical properties and thermal conductivity of XNBR matrix. Especially, in comparison with those of neat XNBR, the tensile strength, tear strength and thermal conductivity of XNBR/GO nanocomposites with 4 phr (parts per hundred rubber) GO3 increased by 114.6%, 88.5% and 27.2%, respectively.